(untitled) (Південний архів (історичні науки), 2022)
The purpose of the article is to analyze key trends in the development of non-Olympic sports and the conditions of its existence, as well as identify the causal links between the field of physical culture and sports and the socialization of the individual. The methods are general scientific methods of logic (analysis, synthesis, etc.). The comparative method is used for the development of Olympic and non-Olympic sports; chronological: for the establishment of stages of development. As a results of the research it is established that the main stages of development were associated with political transformations: the first was from the end of the XIX century to 1917 (pre-revolutionary), the second was from 1921 to 1991 (Soviet) and the third has been from 1991 to the present (Ukrainian). At the beginning of the twentieth century, the inhabitants of the Left-Bank Ukraine were engaged in tiny towns, weightlifting (at that time it was not shared with weightlifting), motorsports, chess, checkers, acrobatics and horse racing. In Soviet times, the development of all sports was subordinated to the state interests, so increased attention was paid to military-technical sports, as well as mental sports. The state encouraged citizens to engage in Olympic and non-Olympic sports. Material and technical conditions were created for the development of numerous sports. A system of teaching staff training was also established. Nowadays, gymnastics (shaping, stretching), sports aimed at strength use of muscle mass (bodybuilding, powerlifting), dance sports (cheerleading, acrobatic rock’n’roll) are successfully developing, extreme sports (underwater sports, skateboarding), national sports (fighting hopak, various types of karate) as well. The influence of physical culture and sports on socialization and sociocultural development of a person is analyzed. It has been proved that sports helped to improve the health of citizens, which was strongly encouraged by the authorities. The sports movement, from the first years of the establishment of Bolshevik rule, acted as a way to the emancipation of women. Involving low-mobile categories of citizens in sports practices helped them to overcome social alienation. In addition, this type of physical activity was a substitute for socially unacceptable forms of behavior. Conclusions. Thus, we can conclude that the process of formation and development of non- Olympic sports took place in three stages and sports practices contributed to the socialization of the individual.